Bamboo-derived porous biochar for efficient adsorption removal of dibenzothiophene from model fuel. (1st January 2018) - Yang, Enbo; Yao, Chunlian; Liu, Yachun; Zhang, Chao; Jia, Litao; Li, Debao; Fu, Zaihui; Sun, Dekui; Robert Kirk, Steven; Yin, Dulin
Graphical abstract: Highlights: The biochar was prepared by ZnCl2 chemical activation and further HNO3 oxidation. The biochar is rich in micropore. The graphitization degree and surface acidic groups can improve its ADS performance. The biochar has a good recycling performance. Abstract: In this work a series of bamboo-derived biochars rich in micropores (its micropore ratio as high as 76%) were prepared by ZnCl2 chemical activation of bamboo processing residues, further modified with oxidation using concentrated HNO3, and characterized by N2 adsorption, XRD, Raman spectra, elemental analysis and Boehm titration. Their adsorptive desulfurization (ADS) performances were examined using dibenzothiophene from model fuels as an adsorbate. The results showed that the pore structure properties of these biochars are dominated by ZnCl2 chemical activation, the graphitization degrees are mainly governed by activation temperature, and the significantly increased surface acidic groups are primarily contributed from the HNO3 oxidation treatment. The biochar's abundant micropore characteristic is an indispensable prerequisite for its good ADS performance, and also its high graphitization degree and surface acidic groups play important roles in improving ADS performance. Meanwhile, the optimized biochar can achieve an sulfur removal (%) of 96% with a selectivity close to 96%, its maximum adsorption amount and its breakthrough capacity reach 38.4 mg-S/g and 9.5 mg-S/g, respectively, and it shows much superior ADS performance to commercial activated carbon (AC) used in this work. Furthermore, the biochar can be reused for three times after regeneration without significant loss of ADS capacity. Thus, the biochar may become an excellent ADS adsorbent for production of clean fuel oils.